Health–economic benefits of treating trauma in psychosis. Issue 1 (31st December 2019) - de Bont, Paul A. J. M.; van der Vleugel, Berber M.; van den Berg, David P. G.; de Roos, Carlijn; Lokkerbol, Joran; Smit, Filip; de Jongh, Ad; van der Gaag, Mark; van Minnen, Agnes
ABSTRACT: Background : Co-occurrence of posttraumatic stress disorder (PTSD) in psychosis (estimated as 12%) raises personal suffering and societal costs. Health–economic studies on PTSD treatments in patients with a diagnosis of a psychotic disorder have not yet been conducted, but are needed for guideline development and implementation. This study aims to analyse the cost-effectiveness of guideline PTSD therapies in patients with a psychotic disorder. Methods : This health–economic evaluation alongside a randomized controlled trial included 155 patients with a psychotic disorder in care as usual (CAU), with comorbid PTSD. Participants received eye movement desensitization and reprocessing (EMDR) ( n = 55), prolonged exposure (PE) ( n = 53) or waiting list (WL) ( n = 47) with masked assessments at baseline (T0) and at the two-month (post-treatment, T2) and six-month follow-up (T6). Costs were calculated using the TiC-P interview for assessing healthcare consumption and productivity losses. Incremental cost-effectiveness ratios and economic acceptability were calculated for quality-adjusted life years (EQ-5D-3L-based QALYs) and PTSD 'Loss of diagnosis' (LoD, CAPS). Results : Compared to WL, costs were lower in EMDR (-€1410) and PE (-€501) per patient per six months. In addition, EMDR (robust SE 0.024, t = 2.14, p = .035) and PE (robust SE 0.024, t = 2.14, p = .035) yielded a 0.052 and 0.051 incremental QALY gain, respectively, as well as 26% greater probability for LoD following EMDR (robust SE = 0.096, z = 2.66, p = .008) and 22% following PE (robust SE 0.098, z = 2.28, p = .023). Acceptability curves indicate high probabilities of PTSD treatments being the better economic choice. Sensitivity analyses corroborated these outcomes. Conclusion : Adding PTSD treatment to CAU for individuals with psychosis and PTSD seem to yield better health and less PTSD at lower costs, which argues for implementation. HIGHLIGHTS: This is the first randomized study ( N = 155) to examine cost-effectiveness of trauma focused therapy (TFT) in psychotic patients. Exposure and EMDR yielded less PTSD, better health and lower costs than a PTSD waiting list. TFT in psychosis is a candidate for clinical guidelines.